Analisis Penerapan TELOS Feasibility Study Sebagai Kriteria Penilaian Kelayakan Investasi pada UMKM: Studi Kasus Inkubator Bisnis di Lampung - Aini Kolbiana; Evony Silvino Violita (Jurnal Maksipreneur: Manajemen, Koperasi, dan Entrepreneurship)
This study aims to provide investment feasibility assessment criteria that can be used to assess MSMEs so they can help increase opportunities to obtain investment. There are no specific regulations regarding investment eligibility criteria for MSMEs in Indonesia, so it’s difficult for various parties to carry out investment activities. The approach is taken through the dimensions of Technical, Economic, Legal, Operational, and Schedule Feasibility Studies (TELOS FS) which are usually used to analyze the feasibility of investing in projects. The object of this research is a business incubator that provides funding for MSMEs. This research used interviews, observation, and document analysis for investee and business incubators. The research results show that using TELOS dimension can be fully utilized with several adjustments. Another result is that TELOS FS can be used for SMEs. For micro businesses technical and operational aspects can be fully assessed, but for using comprehensive aspect assistance/incubation is required to apply TELOS FS as an assessment aspect. This research helps investors to map aspects to assess the feasibility of investing in MSMEs. This research was conducted using qualitative methods for in-depth exploration, but further research using quantitative methods with a larger sampling number is expected to support this research.